Using Technology as Learning Media to Enrich ESP Students' Speaking Skill for Indonesian Higher Education Students - Nurul Amaliah; Sunarlia Limbong; Nur Ina Syam; Fahmi Room; Khaliq Bashar (CV. Eureka Murakabi Abadi, 2023)
For everyone, learning a new language is a really difficult undertaking. It's considerably more difficult to receive an education in a foreign tongue. It takes a lot of time to learn how to read, understand, speak, and write flawlessly in a language. ESL students who attempt to navigate this challenging experience while living abroad encounters numerous language and communication issues. This qualitative case study research project's main goal was to identify the educational technology tools that participants used to advance their language and communication abilities. This study is based on the research question: